2020
DOI: 10.4103/jfmpc.jfmpc_479_20
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hyperparathyroidism and peripheral giant cell granuloma of the jaw: A rare case report

Abstract: Peripheral giant cell granuloma (PGCG) known as “giant cell epulis” is a benign, reactive exophytic gingival lesion that accounts for less than 10% of all gingival lesions. PGCG affects females more than males with middle age predilection. Till now the etiology of PGCG remains unclear but various factors that can cause PGCG include poor oral hygiene, food impaction, following an extraction, dry mouth, hormonal disturbance, and hyperparathyroidism. The reported recurrence rate of the lesion is 5.0%–70.6%. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Moreover, in this study female predilection is shown; posterior mandible is also the main occurring site accounting for 67% of the lesions. Female predilection cloud be related to positive influence of oestrogen and progesterone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, in this study female predilection is shown; posterior mandible is also the main occurring site accounting for 67% of the lesions. Female predilection cloud be related to positive influence of oestrogen and progesterone [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various etiological factors for PGCG such as poor oral hygiene, food impaction, xerostomia, pregnancy, hormonal imbalance, and hyperparathyroidism (HPT) [ 1 , 17 ]. In cases of multiple lesions, both synchronous and metachronous, once removed classic irritating factors, clinicians should suspect hormonal imbalances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations